The Anti-Inflammatory Roles of Vitamin D for Improving Human Health - Aysen Kutan Fenercioglu (Current Issues in Molecular Biology)
Vitamin D receptors (VDRs) are present in almost all cells of the immune system, including B cells, T cells, NK (Natural Killer) cells, dendritic cells, and monocytes, as well as the epithelial cells of many organs such as the intestine, pancreas, prostate, lungs, and cardiomyocytes. In addition, some immune cells, including dendritic cells, macrophages, and B and T cells, can synthesize calcitriol by expressing 1α-hydroxylase. Upon binding to VDRs, vitamin D (Vit D) regulates the expression of genes involved in immune responses, including those encoding for cytokines. It modulates the production of pro-inflammatory cytokines while promoting the synthesis of anti-inflammatory cytokines. Vit D also affects the differentiation and maturation of cells of the immune system. By inhibiting the nuclear factor kappa B (NF-κB) and mitogen-activated protein kinase (MAPK) pathways, Vit D reduces the expression of pro-inflammatory genes. These effects highlight the potential of Vit D as a therapeutic agent in the management of inflammatory diseases, including autoimmune disorders, cardiovascular diseases, diabetes, metabolic syndrome, cancer, neurological diseases, depression, and inflammatory bowel disease.